2015
DOI: 10.1155/2015/817862
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian and Renal Vein Thrombosis: A Rare Cause of Fever Outer the Postpartum Period

Abstract: Although there is no other underlying disease, women can sometimes experience rare and serious diseases such as ovarian vein thrombosis (OVT) and renal vein thrombosis (RVT) after giving birth. The widespread development of thrombosis is treated for the first time in this study. Stasis, coagulation factor abnormalities, and intimal damage to the venous thrombosis risk can increase during pregnancy. It was mentioned that it diagnoses an abnormality in the hypercoagulability half of women with OVT. Despite the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…OVT is a rare venous thromboembolic disease of puerperium that affects 0.05–0.18% of postpartum women [ 1 ]. The underlying pathophysiology of OVT in pregnancy is attributed to Virchow's triad of venous stasis, endothelial damage, and hypercoagulability [ 2 , 3 ]. Other conditions responsible for causing thrombus formation in ovarian vein are malignancies, pelvic inflammatory diseases, sepsis, and pelvic surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…OVT is a rare venous thromboembolic disease of puerperium that affects 0.05–0.18% of postpartum women [ 1 ]. The underlying pathophysiology of OVT in pregnancy is attributed to Virchow's triad of venous stasis, endothelial damage, and hypercoagulability [ 2 , 3 ]. Other conditions responsible for causing thrombus formation in ovarian vein are malignancies, pelvic inflammatory diseases, sepsis, and pelvic surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…It may rarely be idiopathic and occur spontaneously without any identifiable risk factors or underlying hypercoagulable disorders [ 4 , 5 ]. Thrombus occurs in the right ovarian vein in 70–90% of cases, although some authors have reported higher incidence in left ovarian vein as well [ 2 , 6 ]. This increased incidence on right side is due to the longer length and absence of competent valves in right ovarian vein [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exclusion of an infectious aetiology in a postpartum patient with fever was of great importance to us. Fever of unknown origin that persists despite antibiotics is a predictive clue to the formation of thrombus in the postpartum period (Togan et al, 2015). We faced a careful treatment choice challenge successfully and also the matter of which speciality should be responsible for her attendance.…”
Section: Discussionmentioning
confidence: 99%